O emprego do trabalho de campo no ensino de geografia das escolas do Núcleo Regional de Educação de Francisco Beltrão - PR - Caus, Francieli Regina (2015)
The discussions that permeate the Geography Teaching are vast and composed of numerous technical and scientific variables, economic, political and cultural partners requiring significant judgment. In this context, the present study aims to analyze the importance of field work as a methodology for Geography Teaching. In this light, it was searched, within teachers who teach this course at the Education state system of the Regional Education Core in Francisco Beltrão (NRE-FB) and for students in the third year of high school, elements that could help to identify the use and recovery of this methodology in the teaching-learning process. Through gathering, organization and data analysis gathered via questionnaires and interviews with teachers and students,there is a need of understanding if the field work are effectively adopted as a teaching methodology for Geography as an aid in the construction of geographic knowledge as well as their permeate through the universe studied, since its use is planned and guided by the Curriculum Guidelines of Paraná State. The steps for the development and structuring of the research were composed by; bibliographic close about the importance of the Field Work in Geography Teaching and primary data collection. This data consists in the preparation and execution questionnaire analysis for: one hundred sixty-seven teachers Geography Schools of NRE -FB; for two hundred eighty-one students in the 3rd year of high school (in 2014) and for eighteen graduates students of Geography (4th year ofGraduates at UNIOESTE, 2014). These data were supplemented by information arising from interviews obtained from the forty-one teachers from schools belonging to the NRE FB, who declared conduct field work in their classes and interviews with three teachers working with training of geography teachers (UNIOESTE, USP ). Therefore, it was found that in primary and secondary education schools belonging to the NRE - FB, the field work are little made. There are several reasons for this low adherence to methodology by teachers, among the which stands out problems of bureaucratic, financial and curricular order. The research supports the recognition of the potential of Fieldwork methodology has for teaching by the teachers surveyed, likewise, knowledge is not accompanied by effective compliance methodology, being more decisive in this regard, the academic education, or is, the presence of this methodology on the basis of -your teacher education.